Fostering Discipline in Grade 2 Students: The TGT Learning Model: Meningkatkan Karakter Disiplin Siswa SD Kelas 2: Model Pembelajaran TGT - Uud Nur Afidah; Feri Tirtoni (Universitas Muhammadiyah Sidoarjo, 2023)
This study aimed to assess the effectiveness of the TGT (Team Game Tournament) learning model, supported by snakes and ladders media, in improving the disciplined character of grade 2 students at SDN Watutulis 2. Conducted as a classroom action research (CAR) with multiple cycles, the research encompassed pre-cycle activities, cycle 1, and cycle 2. The subjects consisted of 26 grade 2 students (13 boys and 13 girls) from SDN Watutulis 2. Data collection techniques included observation, interview documentation, and self-assessment sheet tests. The pre-cycle results indicated that only 10 students completed the tasks, while 16 did not meet the minimum completeness criteria (KKM) of 75. To address this, cycle 1 was implemented, and following the application of the TGT learning model, 18 students completed the tasks, while 8 did not, resulting in an average score of 80.19 and a completeness percentage of 69.23%. Since 8 students remained incomplete, cycle 2 was initiated. During the second cycle, 23 students completed the tasks, while 23 did not, yielding an average score of 84.42 and a completeness percentage of 88.46%. The findings indicate that the TGT learning model effectively enhances students' discipline character. The implications of this research are discussed in terms of improving teaching practices and student character development. Highlights: Effective intervention: The TGT learning model, combined with snakes and ladders media, serves as an effective intervention to improve disciplined character among grade 2 students. Iterative approach: The research consisted of multiple cycles, allowing for ongoing reflection, adjustments, and improvements in implementing the TGT learning model. Positive outcomes: The application of the TGT learning model led to increased completion rates, higher average scores, and improved discipline character among the grade 2 students involved in the study. Keywords: TGT learning model, disciplined character, grade 2 students, classroom action research, snakes and ladders media.